Gambaran dan Hubungan Konsumsi Air Minum dan Iklim Kerja dengan Dehidrasi Pada Pekerja Konstruksi di Proyek Pembangunan Hotel Soll Marina Tahun 2024 - Rahmawati, Winona; Ernyasih (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2025)
Construction workers in Indonesia occupy a group with a high risk of dehydration due to working conditions in open spaces, exposure to hot sun, and heavy physical activity. The construction workforce numbers more than 8 million people, the majority of whom work in outdoor areas. Indonesia's tropical climate with an average temperature of 26-33°C and humidity above 70% increases the risk of fluid loss and shows that the average drinking water consumption of construction workers is only about 1-1.5 litres per day. This increases the risk of decreased concentration, fatigue, low productivity, and work accidents. This study used quantitative research with a cross-sectional design. The method used was through distributing questionnaires to construction workers and there were 135 respondents in this study. The majority of respondents had poor drinking water consumption patterns (51.9%), while only 65 people (48.1%) consumed sufficient amounts of water according to the standard daily fluid requirements. Then from the aspect of work climate, as many as 82 respondents (60.7%) were stated to work in an unfavourable work climate, while 53 respondents (39.3%) were in a work environment that was categorised as good. Meanwhile, in terms of dehydration status, most respondents were dehydrated. It was recorded that 91 respondents (67.4%) were in a dehydrated condition, while only 44 people (32.6%) The results of this study indicate that low drinking water consumption and climatic conditions are associated with dehydration.